OPTIMALISASI KEMAMPUAN PEMAHAMAN KONSEP MURID SEKOLAH DASAR MELALUI IMPLEMENTASI PENDEKATAN DEEP LEARNING - Nurito, Nurito; Nurpratiwiningsih, Laelia; Melyana Fitri, Rila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of the deep learning approach in improving elementary school students’ conceptual understanding through the Systematic Literature Review (SLR) method. The study was conducted by collecting and synthesizing various relevant scientific articles using the Publish or Perish application integrated with Google Scholar. The article selection process refers to the PRISMA protocol, which includes the stages of identification, screening, eligibility assessment, and final selection. From the initial search results that produced 724 articles, the screening process reduced the number to 503 articles, finally obtaining 13 articles that met the inclusion criteria for in-depth analysis. The result showed that the deep learning approach is effective in improving elementary school students’ conceptual understanding. This improvement is demonstrated through learning outcomes, active student engagement, and thinking and reflection skills. Furthermore, the implementation of deep learning combined with innovative learning models and the use of learning media has been proven to create more meaningful learning. However, several obstacles to its implementation exist, including limited facilities, teacher readiness, and implementation time. Based on the research results, it can be concluded that the deep learning approach has significant potential for improving elementary school students’ conceptual understanding, with the note that optimal support is needed for its implementation.